Safeguarding Reimagined: Centering Athletes’ Rights and Repositioning Para Sport to Chart a New Path - Tuakli-Wosornu, Yetsa A.; Kirby, Sandra L. (Frontiers in Psychology, 2022)
Objectives: Para sport has much to teach the world of sport about safeguarding and athlete protections. By centering the human rights of athletes in safeguarding, and underlining rights-based philosophical underpinnings of the Paralympic Movement, we outline how sport can indeed be safer to all players, coaches, and other sport actors. Methods: We address global Human Rights conventions and their application to Para and non-disabled sport. Safe Sport is positioned as a matter of human rights. The nature of interpersonal violence that human beings experience within and outside sport is also discussed. Best-available evidence about the nature and scope of interpersonal violence within Para sport is also described. The intersectionality of vulnerable identities (related to gender, sexuality, disability etc.) is reviewed in some detail. Results: Rights violations in Para and non-disabled sport illustrate both individual and organizational vulnerabilities. At their root, both are a breach of human rights. Individual and organizational drivers of abuse, as well as varying modes and types of abuse exemplified in Para sport are relevant in all sport settings and should be centered in all sport safeguarding work. The rights-based core of Para sport exemplifies this. Conclusion: From a Para-informed vantage point, the authors issue a call to action to reduce interpersonal violence in sport by leveraging relevant elements of the Paralympic Movement. This call tasks all sport actors and participants to follow the Para sport paradigm. It embodies human achievement (including sporting success), reflecting human rights and inherent human dignity and value, which requires a higher standard of behaviour.